WADY WRODZONEAnatomical correction of transposition of the great arteries with intact ventricular septum in a 7-month-old infant - Mroczek, Tomasz; Wójcik, Elżbieta; Skalski, Janusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Anatomical correction of transposition of the great arteries with intact ventricular septum should be performed in the first three weeks of life. Attempts at anatomical correction in older infants are preceded by pre-training of the left ventricle to function as a systemic ventricle. We present the case of a 7-month-old infant with transposition of the great arteries with intact ventricular septum, in which the anatomical correction was performed after 2-week pre-training of the left ventricle.